PENGARUH BERBAGAI JENIS ZAT PENGATUR TUMBUH TERHADAP PERTUMBUHAN STUMP JATI (Tectona grandis L.F) - Trisna, Nofika; Umar, Husain; Irmasari, Irmasari (Jurnal Warta Rimba, 2013)
This research was aimed to determine the effect of some growing controller materials on the growth of Jati (Tectona grandis L.f) seedlings.The researchwas conducted from April to June 2013,at the Permanent Nursery,Tadulako University, Palu Central Sulawesi. The experiment was laid out in a Randomized Complete Design (RCD) with four treatments, Control that received no growing controller matersials application/control (H0), Atonik 750 ppm (H1), Rootone-F 500 ppm (H2), Coconut juice 10% (H3). Observation parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant. The results of the study showed that there were significant differences between the treatments in all the parameters assessed.The highest seedling height increment (19 cm) was achieved by Atonik 750 ppm treatment while the lowest (14,9 cm) was achieved by control treatment. Similar to the highest stem diameter increment (0,140 cm) was also achieved by Atonik 750 ppm treatment while the lowest (0,110 cm) was achieved by control treatment. Hence, the highest leaf number increment (7,6 pieces) was achieved by Atonik 750 ppm treatment while the lowest (3,6 pieces) was achieved by control treatment. Keywords : Growing controller material, Seedling growth, Tectona grandis L.f